2010
DOI: 10.1103/physrevd.82.083004
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of particles as a universal property of rotating black holes

Abstract: We argue that the possibility of having infinite energy in the centre of mass frame of colliding particles is a generic property of rotating black holes. We suggest a general model-independent derivation valid for dirty black holes. The earlier observations for the Kerr or Kerr-Newman metrics are confirmed and generalized.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
153
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 9 publications
(28 reference statements)
9
153
0
Order By: Relevance
“…Based on their pioneering discussion, the BSW mechanism has been extensively studied for multifarious black holes [2]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their pioneering discussion, the BSW mechanism has been extensively studied for multifarious black holes [2]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…Kerr spin parameter is arbitrarily close to unity and angular momentum of one of the particles takes a specific finetuned value. Various aspects of this process were analyzed by different authors [2][3][4][5][6][7][8][9][10][11][12][13][14]. A similar process in the context of numerous other examples of black holes including Reissner-Nordström black hole [15] was also studied [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 97%
“…Bañados et al [1] and some other authors [2][3][4][5][6][7][8] recently showed that particles falling freely from rest outside a Kerr black hole can collide with arbitrarily high center of mass energy in the limiting case of maximal black hole spin. They proposed that this might lead to signals from ultra high energy collisions, for example of dark matter particles.…”
Section: Introductionmentioning
confidence: 99%